Inventory Of Types And Traditional Cakes In A Series Of Wedding Ceremonies In Nagari Canduang Koto Laweh - Anisa Rahmawati; Wirnelis Syarif (Universitas Negeri Padang, 2021)
The background of this research was motivated by the curiosity of researcher about the accurate science of marriage custom at Nagari Canduang Koto Laweh. The purpose of this research was to identify the types and recipes of traditional cake through the series of wedding ceremony at Nagari Canduang Koto Laweh. The design of this research was qualitative research. The data were collected through observation, interview and documentation. The result of the research showed that the type of ceremony series were maresek, sauah tando, manjapuik marapulai, marapulai pulang, mamanggia minantu, manantuan kandang, baralek, maanta kain, maanta katidiang, mandoa bulan malin, pasinggah buko and maanta pabukoan. The type of tradisional cake served were katan, ajik, pinyaram, kubang, timandi, bareh jao, batiah, goreang pisang, jaguang abuh, kue sapik and kue tangan. The processing tool was divided into preparation tools, molds and countering tools. How to counter the traditional cake depends on the type of series that was being carried out. The way to do this was to dish out with the plate, bereang-bereang and rantang. The meaning of traditional cake was related to the role of leadership in Minangkabau custom and people's life as social being. Tradisional cake recipes in the form of notes about the name, ingredients and how to make traditional cake at the series of wedding ceremony at Nagari Canduang Koto Laweh Candung District.